(untitled) - Byrne, Jody (Netherlands, 2006)
This book is an introduction to technical translation and usability for translators and researchers. It draws on a broad range of research and makes it both accessible and applicable to those involved in the practice and study of translation. After exploring various theoretical aspects of technical translation, readers learn how to improve and assess the quality of technical translations by using cognitive psychology, usability engineering and technical communication to develop skills which can be implemented during the text production stage of the translation process. A practical usability study is described to illustrate the theories, methods and benefits of usability engineering. This book is unique in that it discusses technical translation from a theoretical and practical point of view.
Keywords: Biên dịch và phiên dịch,Ngôn ngữ học ứng dụng,Translating and interpreting,Applied linguistics